The role of hydrogenotrophic methanogens in an acidogenic reactor - Huang, Wenhai (2015)
A laboratory-scale acidogenic anaerobic sequencing batch reactor was set up to test the effect of pH change on microbial community structure of the reactor biomass and process performance. No immediate performance change on acidogenesis was observed after the pH change. However, as the hydrogenotrophic methanogen population decreased, hydrogen content in biogas increased followed by a sharp decrease in volatile fatty acids (VFAs) with acetic acid (HAc) in particular. Recovery of reactor performance following pH correction was only apparent after recovery of hydrogenotrophic methanogen population. These suggested hydrogenotrophic methanogens played a very important role in performance of the acidogenic process.